Analysis of the influencing factors on fine-needle aspiration biopsy results of the thyroid - Wang, Chun-Yan; Zhou, Yan; Ren, Yu-Yuan; Luan, Yu-Shuang; Jiang, Zhong-Cai; Wang, Zhi-Xing (Frontiers in Surgery, 2022)
Objective The objective of the study is to analyze the influencing factors on the results of thyroid fine-needle aspiration biopsy (FNAB). Method A total of 339 patients who underwent FNAB in our hospital from December 2018 to July 2021 were retrospectively selected. The patients were chosen according to the gender ratio, age, and thyroid ultrasound characteristics and were divided into three groups: (1) a 22G needle vacuum aspiration group (Group 1, n = 85), (2) a 22G biopsy needle non-vacuum aspiration group (Group 2, n = 50), and (3) a 25G biopsy needle non-vacuum aspiration group (Group 3, n = 204). Patients in these groups were evaluated for determining the FNAB dissatisfaction rate of pathological samples. A bivariate regression analysis of independent risk factors related to the unsatisfactory pathological diagnosis of samples was performed. Results The specimen dissatisfaction rates of the three groups were 22/85 (25.9%), 15/50 (30%), and 18/186 (9.7%), respectively. The overall sample dissatisfaction rate was 55/339 (16.2%), and the sample satisfaction rate of Group 3 was higher than that of Groups 1 and 2 (P < 0.05). Logistic bivariate regression analysis showed that the age of the patients and the capillary sampling needles and aspiration methods were two independent risk factors for determining the dissatisfaction rate of FNAB pathological samples. Conclusion A 25G capillary sampling aspiration biopsy needle was selected to perform FNAB in thyroid nodules without vacuum aspiration, which could effectively improve the accuracy of FNAB results with a high specimen satisfaction rate.